2014
DOI: 10.1017/s0899823x00194073
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Healthcare-Associated Pneumonia: Worse Disease or Sicker Patients?

Abstract: Background.Healthcare-associated pneumonia (HCAP) is an entity distinct from community-acquired pneumonia (CAP). HCAP has a higher case-fatality rate, due either to HCAP organisms or to the health status of HCAP patients. The contribution of HCAP criteria to case-fatality rate is unknown.Methods.We conducted a retrospective review of adult patients admitted with a diagnosis of pneumonia from July 2007 through November 2011 to 491 US hospitals. HCAP was defined as having at least 1 of the following: prior hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…However, the complication rate was higher among patients with HAP compared to CAP. These findings are matched with the results of a study done by Rothberg et al, which revealed that the case-fatality is greater with HAP since they were more likely to have a principal diagnosis of sepsis and respiratory failure than CAP patients 14. This can be explained by numerous influencers such as the different organisms that cause HAP, immune status, comorbidities, and current use of medication.…”
Section: Discussionsupporting
confidence: 87%
“…However, the complication rate was higher among patients with HAP compared to CAP. These findings are matched with the results of a study done by Rothberg et al, which revealed that the case-fatality is greater with HAP since they were more likely to have a principal diagnosis of sepsis and respiratory failure than CAP patients 14. This can be explained by numerous influencers such as the different organisms that cause HAP, immune status, comorbidities, and current use of medication.…”
Section: Discussionsupporting
confidence: 87%
“…We classified pneumonia as community acquired or healthcare associated using the methodology used by other authors. 32,33…”
Section: Methodsmentioning
confidence: 99%
“…9 Because of the potentially fatal complications associated with elderly trauma patients who contract PNA, we admit these patients to our surgical ICU. Therefore, we included both PNA and INT as markers for admission in our facility's scoring system.…”
Section: Methodsmentioning
confidence: 99%